Performance of Nagpur mandarin (Citrus reticulata Blanco) under different levels of fertigation and soil applications - PIMPALE, A.R.; KHARCHE, V.K.; PANCHBHAI, D.M.; WADATKAR, S.B. (Journal of Soil and Water Conservation, 2022)
A field experiment to study the effect of different levels of fertigation and soil application of fertilizers on growth, yield and quality of 10 year-old bearing Nagpur mandarin crop (Citrus reticulata Blanco) was conducted during 2015-18 at progressive farmer’s field in Nimaji village, Kalameshwar taluka of Nagpur district in Maharashtra, India by College of Agriculture Nagpur. The experiment was laid out in randomised block design consisting of six treatments and four replications. The treatments comprised of one soil application treatment of RDF (Recommended dose of fertilizers) and five treatments of fertigation with 115%, 100%, 85%, 70% and 55% of RDF, respectively. Soil application was done in two splits as per the recommendations and fertigation doses were applied in six splits as per requirement of nutrients. The pooled analysis of the observed data was carried out. Fertigation with 115% RDF showed maximum values of the growth parameters like increase in plant height (0.582 m), increase in stock girth (6.05cm), increase in plant spread (0.579 m) and increase in canopy volume (18.21 m3) which were statistically at par with fertigation with 100% RDF and 85% RDF, respectively. Fertigation with 85% RDF showed maximum values in regards to number of fruits, average fruit weight and actual fruit yield in terms of kg/plant (596,168.22 g, 100.13 kg/plant). However, these values were statistically at par with fertigation at 100% of RDF (595,166.16 g, 98.86 kg/plant) and fertigation with 115% RDF (592, 164.61g, 97.42 kg/plant). Highest fruit yield (27.74 t/ha) of Nagpur mandarin crop was recorded in fertigation with 85% RDF followed by fertigation with 100% RDF (27.38 t/ha) and 115% of RDF (26.99 t/ha), respectively. However, these yields were statistically at par. Fertigation with 85% RDF showed highest value of TSS (11.17 °Brix), lowest value of acidity (0.798 %) and maximum TSS: Acidity ratio (13.97) indicating best quality parameters followed by fertigation with 100% RDF (11.05 °Brix, 0.808% and 13.71, respectively). Juice content (50.97%) in fertigation with 85% RDF was found to be significantly superior over all other treatments. Maximum benefit cost ratio of 3.20 was obtained in fertigation with 85% RDF followed by fertigation with 100% RDF(2.99) and 115% RDF(2.85), respectively. The sustainable production of Nagpur mandarin was obtained by fertigation technology with 85% RDF (1020–340–510 NPK g/plant) in 6 given splits with saving of 15% fertilizers and 23.6% increase in yield over soil application of fertilizers. This fertigation dose should be split into six parts as per the growth of fruits.